Mexican birds use according to environmental officers - Roldán-Clarà, Blanca; López-Medellín, Xavier; Calderón de la Barca, Nelly; Leyva, Claudia; Espejel, Ileana (Ethnobiology and Conservation, 2017)
Birds are used in México for subsistence income and have traditionally been part of local cultural heritage. A group of people called pajareros are required by law to apply for permits for harvesting and selling birds, which are authorized by Mexican environmental and wildlife government officers mostly for subsistence use. While environmental manager officers interact with stakeholders as part of their work, how they actually interrelate with pajareros and make final decisions remains unclear. Therefore, we describe regulation of bird use in Mexico, analyze criteria applied, and provide the opinions of the four key officers involved in natural resource management obtained in open interviews held during 2012. Officers have a stereotyped view about pajareros and a close, sometimes conflicting relation with them, express good knowledge of social-environmental conflict related with songbirds, and decide songbird harvest rates based on the three pillars of sustainability, but prioritizing environmental laws over social needs.